An Automated Process for Layer‐by‐Layer Assembly of Polyelectrolyte Multilayer Thin Films on Viable Cell Aggregates. Issue 2 (4th September 2012) - Mets, Joseph M.; Wilson, John T.; Cui, Wanxing; Chaikof, Elliot L.
<x xml:space="preserve">Abstract</x> An automated process for modifying the surface of pancreatic islets grows uniform polyelectrolyte multilayer thin films, eliminating user variability associated with previous manual methods. Machine vision feedback allows for tight control of small fluid volumes, maintaining an islet microenvironment. This process is adaptable to other fragile micrometer‐scale particle systems. <boxed-text content-type="graphic" position="anchor" orientation="portrait"> </boxed-text>